2018
DOI: 10.1002/ajhb.23142
|View full text |Cite
|
Sign up to set email alerts
|

Child participation in sports is influenced by patterns of lifestyle‐related behaviors

Abstract: Future interventions to promote children's participation in sports should be based on a socio-ecological model and targeted to high-risk populations showing multiple risks such as a lower socio-economic status, inactive parents, or obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Of the 17 articles identified, one was excluded as it was only published in Spanish, 42 one as it was only an abstract, 43 one as the socioecological model was a recommendation but not part of the research design or analysis 44 (Figure 2). Three more were excluded as they were literature reviews or commentaries and thus not empirical research 45‐47 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 articles identified, one was excluded as it was only published in Spanish, 42 one as it was only an abstract, 43 one as the socioecological model was a recommendation but not part of the research design or analysis 44 (Figure 2). Three more were excluded as they were literature reviews or commentaries and thus not empirical research 45‐47 .…”
Section: Resultsmentioning
confidence: 99%
“…PA participation patterns and influential factors in studies were different due to participants' age, which were basically categorized as children and adolescent cohorts. In studies that included children, parental support [5,6,53,70,71,76,78], and neighborhood environments [8,62,68] were dominant influential factors in children's non-organized PA participation. Among studies with adolescent participants, PA participation was affected by more internal factors: PA enjoyment and self-efficacy [56,59,74,80] and social interactions [52,54,55,58,60,64,69,77].…”
Section: Differences Between Children and Adolescentsmentioning
confidence: 99%
“…A physically active parent was significantly associated with girls' and boys' PA and/or sports participation. Parents' gender was found to be a strong factor in children and adolescents' PA participation [8,53,71,78]. In addition, parental modeling of PA before adolescence and logistic support during adolescence could help girls establish early patterns of PA habits [5], and girls who perceived a more supportive home PA environment were more physically active [62].…”
Section: Microsystemmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2008, the percentage of households with children that have been unable to buy meat or fish every second day has more than doubled during the economic crisis in countries such as Estonia, Greece, Italy and Portugal (27), and data from the Portuguese National Health Surveys revealed that the consumption of soup, fish and meat significantly decreased between 2005 and 2014 (28). The economic crisis may have reinforced the socioeconomic disparities in obesity related behaviors previously reported for Portuguese children, namely that children from lower-SEP had higher odds of consuming saturated and fat diets(29) and less probability of participating in extracurricular sport activities(30).…”
mentioning
confidence: 97%